Decision Support System for New Employee Admission at PT XYZ - Apriyanto, Budi; Fathoni, Azhar (PT FORMOSA CENDEKIA GLOBAL, 2024)
The process of recruiting new employees is one of the important aspects in a company to get the right individuals to fill open positions. PT XYZ, as a company engaged in Transportation services is faced with challenges in the recruitment process of new employees which is still carried out conventionally. This causes a process that takes a long time, is less objective, and has the potential to cause bias. Therefore, this research aims to develop a Decision Support System (SPK) to help PT XYZ in the process of recruiting new employees.